Implementation of Preconception Care: A Scoping Review - Agusta, Nabila Seilla; Astuti, Andari Wuri (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2025)
Background: Preconception services provide women with a variety of programs that start when they are teenagers and continue through pregnancy. These programs are designed to ensure a healthy pregnancy. A well-prepared pregnancy is less likely to cause problems for both mother and child. Approximately 800 women died every day in 2020, contributing to a Maternal Mortality Rate (MMR) of 223 for every 100,000 live births. By 2030, the Sustainable Development Goals (SDGs) will reduce the MMR to 70 per 100,000 live births. Strengthening healthcare systems especially for preconception services are urgent to reduce maternal and child health risks. Supporting projects that aim to improve the accessibility and quality of preconception and other reproductive health services is something the World Health Organization is doing to fill the gaps that exist in these areas. Purpose: The following research efforts aim to provide a comprehensive picture of the implementation of preconception care. Methods: This study used a scoping review method that goes through several stages, including (1) Identifying scoping review questions, which refer to the PCC framework; (2) Identifying relevant articles using three databases (PubMed, Ebsco, and ScienceDirect) with keywords (implementation*) and (preconception*) or (preconception care*) and (expectant parent*). (3) Selection of articles, 303 articles were obtained which were then filtered into 6 articles; (4) Data charting and quality assessment of articles using Mixed Methods Appraisal Tools (MMAT); and (5) Presentation of data/results, discussion, and conclusions. Conclusion: Preconception services can help identify potential problems in women and men that could potentially hinder the couple from obtaining a pregnancy. Couples can be given treatment when problems are found, to prepare a safe and heathy pregnancy. Lack of awareness, unsupportive facilities, and expensive service fees become obstacles. Policies and roles of various parties are needed to support and improve the quality of preconception care.